DNA methylation is reconfigured at the onset of reproduction in rice shoot apical meristem - Asuka Higo (Nature Communications, 2020)
The shoot apical meristem of flowering plants transitions from forming leaves to floral organs. Here Higo et al. show that DNA methylation of many transposons that are hypermethylated in gametes is established in the SAM before flowering, suggesting it protects against harmful transposition long before germ cell differentiation.